Konflik Rumah Tangga dan Strategi Penyelesaiannya dalam Perspektif Hukum Keluarga Islam: Studi di Kota Tual - Taufik Hamud; Hasbollah Toisuta; Eka Dahlan Uar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This research analyzes the forms of household conflicts and their resolution strategies in Tual City from the perspective of Islamic family law. The high divorce rate in Tual City is a concerning phenomenon, with dominant factors including economic conflicts, recurrent quarrels, infidelity, domestic violence (DV), and interference from extended families which actually exacerbates the situation. This research employs a qualitative method with a normative-empirical approach. Primary data were obtained through in-depth interviews with married couples, religious leaders, and traditional leaders in Tual City, and were analyzed together with secondary data in the form of Tual Religious Court decisions of 2023 (Numbers 33, 34, 36, and 37/Pdt.G/2023). The findings indicate that household conflicts in Tual City possess distinctive characteristics influenced by socio-cultural structures, kinship systems (fam), and the still-strong Kei customs. From the perspective of Islamic law, conflict resolution mechanisms through mau’izhah (admonition), hajr (temporary separation), and tahkim (family mediation) are acTually relevant to be applied; however, their implementation has not been optimal due to misconceptions and excessive family interference. This research concludes that the effectiveness of Islamic law-based conflict resolution heavily depends on the couple's understanding, the objectivity of family members, and the professionalism of mediators. The research recommendations include strengthening family education, professionalizing mediation, and fostering collaboration among religious leaders, traditional leaders, and the regional government.